Agricultural tractor performance fueled with proportions of biodiesel - Iamaguti, Priscila Sawasaki [UNESP]; Lopes, Afonso [UNESP]; Pinto, Antonio Alves [UNESP]; Lira, Thyago Augusto Medeiros [UNESP]; de Lima, Leomar Paulo (FapUNIFESP (SciELO), 2022)
Among the fuel sources used nowadays, biofuels stand out for being renewable and biodegradable. In this sense, this work aimed to evaluate the performance and smoke opacity of an agricultural tractor in soil tillage activities, depending on the biodiesel blends and the engine rotation. Were used six blends of soy (S) and murumuru (M) biodiesel and seven engine rotation speeds. The results showed a directly proportional relationship between the drawbar power and the engine rotation decrease. Regarding hourly volumetric and weighted consumption, both presented the same behavior: the lowest consumptions were reached when using the two highest proportions of murumuru biodiesel, yet the highest specific consumption was obtained when using the 90M10S blend. Furthermore, the lowest opacity was emitted when the tractor was fueled with the three blends having the highest proportions of murumuru biodiesel. Blends with more than 80% of murumuru biodiesel promote lower fuel consumption than blends with a higher concentration of soy biodiesel. Regardless of the biodiesel blend, the traction force at the drawbar is directly proportional to an increase in the engine rotation speed. In smoke opacity, mixtures with more than 70% murumuru biodiesel promote less opacity than mixtures with a higher concentration of soy biodiesel
Keywords: Astrocaryum murumuru; Fuel consumption; Glycine max; Smoke opacity